Metals and Metal Alloys and their Enhanced Properties for Jewelry Applications - Supansomboon, Supitcha; Wongsriruksa, Supinya; Watcharatpong, Teerat; Munpakdee, Anocha; Phinichka, Natthapong (Science Essence Journal, 2020)
Jewelry can be made with a wide range of materials, including metal, which is one of the most fashionable materials. Metal jewelry has been used for many centuries due to the attractive and outstanding properties of them. However, there are still limitations for using metals in jewelry, even though metal jewelry has been enhanced and developed continuously in order to reduce the limitations as well as to satisfy the customer needs. In this review article, there are three main groups of metals that are trendy and be able to improve their properties for jewelry application; (i) Precious metals used for Fine Jewelry including gold, platinum, silver and their alloys, (ii) Base metal used for Costume Jewelry or Fashion Jewelry including copper and its alloys and (iii) Other metals for Alternative Jewelry including Titanium and Stainless Steel. The main enhancement properties in metals are alloying elements, which improve their mechanical and physical properties with concerning the hypoallergenic and purity of metals particularly Fine Jewelry. Furthermore, selecting and developing suitable jewelry processing are other important issues to be considered.